Calvyn oor die leiding van die Heilige Gees in die verklaring van die Skrif - P. C. Potgieter (Acta Theologica)
Many theologians are unmistakenly reluctant to acknowledge the guidance of the Holy Spirit as a hermeneutic key in explaining Scripture. This article examines the role of the Spirit in John Calvin’s exegetical method. While he firmly believed in the divine inspiration and clarity (claritas) of the Bible, he also recognised the total depravity of mankind. He therefore concluded that only by illuminating their minds through the Holy Spirit will human beings be able to understand the true meaning of Scripture. By investigating relevant sections of his published works, in particular those in his commentaries on Biblical passages referring to the guidance of the Holy Spirit, this article explores the way in which Calvin established and applied his modus operandi.